Malay Culture History in the Shots Sharia - Indra Gunawan (Akademika: Jurnal Keagamaan dan Pendidikan, 2016)
“Unknown, therefore unloved”, “Tak Tak Cinta Sayang So”. This phrase became the basis of the author writing a paper about getting to know the culture of the nation itself, especially the Malay culture. Similarly, many generation who do not know even forgetting the culture of his own people. Therefore, this paper tries to remind us all, especially the generation now to get closer to culture. The results showed that the cultured, then someone will come appreciate what has been championed by the heroes and parents earlier. And with the memory of its own culture, customs realize meaningfully participate in accordance with the guidance of the Shari’ah. As the saying goes, “Indigenous jointed Personality Personality” jointed ‘Book of Allah’. Hopefully this article provides benefits to the reader as well.